2018
DOI: 10.1111/age.12645
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable genetic diversity detected at river buffalo prolactin receptor (PRLR) gene and association studies with milk fatty acid composition

Abstract: Prolactin is an anterior pituitary peptide hormone involved in many different endocrine activities and is essential for reproductive performance. This action is mediated by its receptor, the prolactin receptor, encoded by the PRLR gene. In this study, we sequenced and characterized the Mediterranean river buffalo PRLR gene (from exon 3 to 10), and we found remarkable genetic diversity. In particular, we found 24 intronic polymorphisms and 13 exonic SNPs, seven of which were non-synonymous. Furthermore, the pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…Recently, other fundamental genes for milk traits have been positively associated with OBCFA in river buffalo. For instance, Cosenza et al (2017) found higher contents of these FA associated with the SNP g.129C>T (P < 0.0006) at the oxytocin receptor gene (OXTR), whereas the marker g.11188A>G at the prolactin receptor gene (PRLR) tended to have a significant effect (P < 0.06) on the same traits (Cosenza et al, 2018). This class of FA in milk fat are mostly derived from rumen bacteria, although linear odd-chain FA might be synthesized de novo in the mammary gland (Vlaeminck et al, 2006).…”
Section: Abmentioning
confidence: 99%
“…Recently, other fundamental genes for milk traits have been positively associated with OBCFA in river buffalo. For instance, Cosenza et al (2017) found higher contents of these FA associated with the SNP g.129C>T (P < 0.0006) at the oxytocin receptor gene (OXTR), whereas the marker g.11188A>G at the prolactin receptor gene (PRLR) tended to have a significant effect (P < 0.06) on the same traits (Cosenza et al, 2018). This class of FA in milk fat are mostly derived from rumen bacteria, although linear odd-chain FA might be synthesized de novo in the mammary gland (Vlaeminck et al, 2006).…”
Section: Abmentioning
confidence: 99%
“…Marker-assisted selection is a useful approach to assist animal breeding. Recently, candidate genes harboring single nucleotide polymorphisms (SNP) significantly associated with milk fat content (Li et al, 2018c;Gu et al, 2019), protein percentage (Manzoor et al, 2018(Manzoor et al, , 2020, and fatty acid composition (Cosenza et al, 2017(Cosenza et al, , 2018 have been identified on different buffalo chromosomes. As for milk yield, one of the most important economic traits in buffalo industry, associated polymorphisms have been identified at the whole genome level (Wu et al, 2013;Venturini et al, 2014;de Camargo et al, 2015;Menon et al, 2016;El-Halawany et al, 2017;Iamartino et al, 2017;da Costa Barros et al, 2018;Du et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although most previous studies concluded that c.836T>A could be a causative SNP for the observed milk production and composition traits, we could not exclude the effects of other linked SNPs in the GHR (such as c.380G>A) or other genes in regions close to c.836T>A locus. A good example of these close genes is PRLR, which locates approximately 7 Mb from the GHR and its SNPs associated with milk yield, and fat and protein content in cattle [8,37]. Both GH and PRL hormones play a crucial role in the initiation and maintenance of lactation in addition to the development of the mammary gland and the development of their genes from a common ancestral gene [33,38].…”
Section: Association Of Ghr Polymorphisms With Gene and Protein Exprementioning
confidence: 99%